The Optimal Control of Mathematical Models for Monkeypox Spread Using the Pontryagin Maximum Principle with Numerical Solution RK6 on Study in Indonesia: engglish - side, syafruddin; Yusuf SAP, Andi Muh. Ridho; Musfira, Musfira; Abdy, Muhammad (Jurusan Matematika FMIPA UNM, 2025)
This study examines the SIQR mathematical model by applying the Pontryagin Maximum Principle (PMP) and the 6th order Runge-Kutta (RK6) numerical solution to the spread of Monkeypox in Indonesia. This study aims to analyze and simulate the dynamics of the spread of Monkeypox and identify optimal control strategies that are effective in suppressing the rate of infection. This study has a population of 283,487,843 individuals. The results of this study show the effectiveness of implementing optimal control in reducing the spread of Monkeypox in the region. This study makes a significant contribution to the development of more efficient and targeted health policies in dealing with Monkeypox outbreaks, and offers valuable insights for future infectious disease control strategies.